FASILITAS SANITASI DI PASAR WONOKROMO SURABAYA TAHUN 2013 - Dewi Anisa; Rusmiati .; Darjati . (Poltekkes Kemenkes Surabaya, 2015)
A market is the place for the sale and purchase of goods with more than one merchant. It includesshopping centers, traditional markets, shops, malls, palazas, trade centers or other designations.Sanitation conditions are among the important factors in the running of market and poor hygienemay result in a wide range of unfavorable consequences, such as transmission of diseases andvector development. The purpose of the present study was to assess conditions of sanitaryfacilities, including locations, buildings, sanitation, clean and healthy behavior (CHB), security andother facilities of Wonokromo Market Surabaya.The study was a descriptive research. Data were collected by observations, interviews andmeasurements using a healthy market form. Variables included location, buildings, clean waterbathrooms and toilets, waste management, drainage, sinks, animal-borne diseases of vectors, CHBof the merchants and market management, market disinfections, security and other facilities. Datawere calculated for percentage and assingned to healthy, less healthy and unhealthy categories.In overall, conditions of sanitation facilities of Wonokromo Market Surabaya were categorized asunhealthy with a score of 5698 out of a variables, the variables locations and security were categorized as less healthy (66%, 60% and 64%, respectivety) and the variable other facilities was categorized as unhealthy (56%).It is recommended to check, improve and add sanitation facilities or other facilities in accordancewith Regulation of the Health Minister No.519/Menkes/SK/VI/2008 on Guidelines forImplementation of Health Markets.